The neutrino floor: a data-driven analysis - Papoulias, Dimitrios K. (HNPS Advances in Nuclear Physics, 2023)
We reconsider the discovery limit of multi-ton direct detection dark matter experiments in the light of recent measurements of the coherent elastic neutrino-nucleus scattering process. Assuming the cross section to be a parameter entirely determined by data, rather than using its Standard Model prediction, we use the COHERENT CsI and LAr data sets to determine WIMP discovery limits. Being based on a data-driven approach, the results are thus free from theoretical assumptions and fall within the WIMP mass regions where XENONnT and DARWIN have best expected sensitivities. We further determine the impact of subleading nuclear form factor and weak mixing angle uncertainties effects on WIMP discovery limits. We point out that these effects, albeit small, should be taken into account. Moreover, to quantify the impact of new physics effects in the neutrino background, we revisit WIMP discovery limits assuming light vector and scalar mediators as well as neutrino magnetic moments/transitions. We stress that the presence of new interactions in the neutrino sector, in general, tend to worsen the WIMP discovery limit.